Samarium (III) oxide thin film as a saturable absorber for the passively Q-switched Tm-doped fiber laser - Rusdi, K.N.; Hisyam, Mohamad Badrol; Mohd Rusdi, Muhammad Farid; Zulkipli, Nur F.; Abdul Latiff, Anas; Harun, Sulaiman Wadi; Saidin, Norazlina (IOP Publishing, 2019)
We have demonstrated a passive Q-switched Thulium-doped fiber laser (TDFL using samarium oxide (Sm2O3) nanomaterial as saturable absorber (SA). The Sm2O3 based SA was fabricated by simply mixing the Sm2O3 powder solution with polyvinyl alcohol (PVA) solution. The homogeneously mixed solution was spread and dry to form a thin film. A piece of 1 mm x 1 mm of the SA thin film is sandwiched between two fiber ferrules and incorporated into a TDFL ring cavity for pulses generation. By controlling the loss and gain in the cavity, stable Q-switching operation was generated. The repetition rate was tunable from 17.62 kHz to 29.20 kHz by varying the pump power from 619 mW to 784 mW. The smallest pulse width of 3.54 µs and the highest pulse energy of 0.20 uJ were obtained at the highest pump power.